Retrofication of Cascade Control System and Implementation of Human Machine Interface in A Water Treatment Plant - Erwin Sitompul; Dicky Kuswira (Journal of Electrical And Electronics Engineering, 2016)
In Indonesia urban area, due to low water distribution pressure at day, many inhabitants who live far from water distribution center get their fresh water share only at night or sometimes never. In order to ensure even distributed fresh water, there is a certain pressure that needs to be maintained. On a real technical project, an advance cascade controller will be installed in a water treatment plant to control multiple pump for maintaining distribution pressure. Furthermore, a corresponding Human Machine Interface (HMI) will be installed for easier daily monitoring and operation. Measurement data shows improved performance of the system, with only 0.02 bar of pressure error and better load distribution among the operating pumps. Keywords: water treatment plant, cascade controller, Human Machine Interface